Trade, Inequality, and the Political Economy of Institutions - Do, Quy-Toan (World Bank, Washington, DC, 2012)
The authors analyze the relationship between international trade and the quality of economic institutions such as contract enforcement, rule of law, or property rights. The literature on institutions has argued, both empirically and theoretically, that larger firms care less about good institutions and that higher inequality leads to worse institutions. Recent literature on international trade enables the authors to analyze economies with heterogeneous firms, and argue that trade opening leads to a reallocation of production in which large firms grow larger, while small firms become smaller or disappear. Combining these two strands of literature, the authors build a model that has two key features. First, preferences over institutional quality differ across firms and depend on firm size. Second, institutional quality is endogenously determined in a political economy framework. They show that trade opening can worsen institutions when it increases the political power of a small elite of large exporters that prefer to maintain bad institutions. The detrimental effect of trade on institutions is most likely to occur when a small country captures a sufficiently large share of world exports in sectors characterized by economic profits.